Occurrence of extended-spectrum β-lactamase, AmpC, and carbapenemase-producing genes in gram-negative bacterial isolates from human immunodeficiency virus infected patients - Marimuthu Ragavan Rameshkumar; Narasingam Arunagirinathan; Balasubramanian Senthamilselvan; Chinnambedu Ravichandran Swathirajan; Sunil Suhas Solomon; Ramachandran Vignesh; Pachamuthu Balakrishnan; Reem M. Aljowaie; Khalid S. Almaary; Tse-Wei Chen (Elsevier, 2021)
Background: Progressive decline of immune response in HIV patients makes them susceptible to frequent bacterial infections. High usage of antibiotics influences the emergence of multidrug-resistant bacteria and worsens the clinical outcomes. In this study, the occurrence of drug-resistant genes in Gram-negative bacterial isolates from HIV patients in South India was analyzed. Methods: A total of 173 Gram-negative bacterial (GNB) isolates from HIV patients were screened for antibiotic susceptibility profile using the Kirby-Bauer diskdiffusion method. Positivity of drug-resistant genes was analyzed using polymerase chain reaction method. Results: In this study, 72.8% of bacterial isolates were obtained from urine specimens, and Escherichia coli (47.4%) was the predominantly isolated bacterium. Overall, 87.3% and 83.2% of GNB were resistant to 3rd generation cephalosporin antibiotics such as cefotaxime and ceftazidime, respectively, 56.6% were resistant to cephamycin (cefoxitin) and 43% to carbapenem (imipenem) antibiotics. Extended-spectrum β-lactamases (ESBL) production was noted among 79.5% of GNB isolates, followed by AmpC (57.1%) and Metallo β-lactamases (37.3%). Molecular analysis revealed that ESBL genes such as blaTEM (94.1%), blaCTX-M (89.2%), and blaSHV (24.2%) were detected at higher levels among GNB isolates. Carbapenemase-producing genes such as blaOXA-48 (20%), blaOXA-23 (2.6%), and both blaOXA-23 and blaOXA-51 like genes (2.6%) and AmpC producing genes such as blaCIT (26.7%), blaDHA (3.6%), and blaACC (1.8%) were detected at low-level. Conclusions: This study concludes that ESBL producing genes are detected at high level among gram-negative bacterial isolates from HIV patients in South India.